Persuasive Communication Strategy in Supporting Sustainable Tourism Development in the North Bandung Area - Desiana, Rahmatika; Novianti, Evi; Khadijah, Ute Lies Siti (Budapest International Research and Critics University, 2021)
This study aims to examine the developers' efforts, the community, and the government in dealing with sustainable tourism areas in the area of North Bandung. This study also seeks to find each institution's communication strategies to find out what kind of procedures can help develop sustainable tourism in the area. Researchers' method is the exploratory method to explore broadly about the causes that influence the occurrence of something. This exploratory research was conducted qualitatively to know the procedures adopted by the parties involved for the continuity of tourism in North Bandung. Causes of disruption of conservation: The natural tourism area in North Bandung is mainly due to the indifference of those who benefit from tourism's short-term benefits. By handling persuasive communication, integrative development emerged and began to be socialized with the community. Persuasive communication is an effective way to integrate agencies on one goal, namely, sustainable tourism development. What primarily drives this compelling communication activity is the existence of cross-sectoral programs carried out by various parties. The results of this study can provide useful information to help improve sustainable tourism programs in an area. This information can help the government, especially regional governments and the ministry of tourism, and the ministry of environment to be followed up concerning programs and human resources in establishing sustainable tourism areas.